Endothelial Microparticles and Systemic Complement Activation in Patients With Chronic Kidney Disease. Issue 14 (17th July 2018) - Jalal, Diana; Renner, Brandon; Laskowski, Jennifer; Stites, Erik; Cooper, James; Valente, Karissa; You, Zhiying; Perrenoud, Loni; Le Quintrec, Moglie; Muhamed, Ismaeel; Christians, Uwe; Klawitter, Jelena; et al.
Abstract : Background: Endothelial microparticles are associated with chronic kidney disease (CKD) and complement activation. We hypothesized that the complement pathway is activated in patients with CKD via endothelial microparticles and that complement activation correlates with endothelial dysfunction in CKD. Methods and Results: We analyzed complement data of 30 healthy subjects, 30 patients with stage III/IV CKD, and 30 renal transplant recipients with stage III/IV CKD, evaluating the potential correlation of complement fragments with brachial artery flow–mediated dilation, Chronic Kidney Disease Epidemiology Collaboration glomerular filtration rate, and urinary albumin/creatinine ratio. Endothelial microparticles were characterized via proteomic analysis and compared between study groups. Complement fragment Ba was significantly increased in CKD and post–kidney transplant CKD. Plasma Ba levels correlated significantly with lower brachial artery flow–mediated dilation, lower Chronic Kidney Disease Epidemiology Collaboration glomerular filtration rate, and higher urinary albumin/creatinine ratio. Factor D levels were significantly higher in the plasma microparticles of patients with CKD versus healthy controls. Plasma microparticles isolated from patients with CKD and containing factor D activated the alternative pathway in vitro. Conclusion: The alternative complement pathway is activated in CKD and correlates with endothelial dysfunction and markers of CKD. Future studies are needed to evaluate whether endothelial microparticles with increased factor D play a pathologic role in CKD‐associated vascular disease. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02230202.